Hieracia balcanica XI. Typification of the Josef Rohlena’s Hieracium (Asteraceae) names from Montenegro - Szelag, Zbigniew (Phytotaxa, 2015)
Josef Rohlena (1874–1944) was one of the most renowned Czech botanists of his time. For more than 40 years he carried out floristic research in the territory of Montenegro, in the central part of the Balkan Peninsula (Pulević 2005). In 1942, Rohlena published his Conspectus florae Montenegrinae, where he summarized 2817 vascular plant taxa (including 2623 species) (Pulević & Karaman 1996), among them 44 Hieracium (Linnaeus 1753: 799) taxa described earlier from Montenegro together with Karl Hermann Zahn (1909), monographer of the genus Hieracium. The major part of Rohlena’s collection is stored at the herbarium of the Charles University in Prague (PRC). Other important sets of his specimens are also housed at the National Museum in Prague (PR).